Midwifery Care for G1P0A0 Pregnant Women with Tomato Juice Administration to Reduce Hypertension in Pregnant Women at PMB Rismala, Asahan Regency - Nurmala Sari; Dwi Septia Nabila; Riska Septiana (Jurnal EduHealth, 2025)
Hypertension during pregnancy is one of the complications that can endanger the health of the mother and fetus. The prevalence of hypertension in pregnant women in Indonesia reaches 6.5% and is the leading cause of maternal mortality. Tomatoes contain potassium, lycopene, and antioxidants that can help lower blood pressure naturally. This study aims to determine the effectiveness of tomato juice administration in reducing hypertension in G1P0A0 pregnant women at PMB Bd. Rismala Siagian, S.Keb., Sei Alim Hasak, Sei Dadap District, Asahan Regency. This study used a case study method with a comprehensive midwifery approach using Varney's 7-step management. The study subject was one primigravida pregnant woman with hypertension at 31 weeks of gestation. The intervention involved administering 200-300 ml of tomato juice per day for a specific period. Blood pressure measurements were taken periodically to evaluate the effectiveness of the intervention. Regular administration of tomato juice resulted in a decrease in blood pressure in the pregnant woman. Systolic and diastolic blood pressure decreased significantly after regular consumption of tomato juice. No adverse side effects were found during the intervention. Tomato juice administration is effective as a complementary therapy in lowering blood pressure in pregnant women with hypertension. Tomato juice can be a safe, easily available, and economical non-pharmacological therapy alternative for treating mild hypertension in pregnancy.